Realization and swimming performance of the breaststroke by a swimming humanoid robot - Nakashima, M.; Kuwahara, K. (ROBOMECH journal, 2016)
In order to clarify the mechanics of human swimming, a full-body swimming humanoid robot called "SWUMANOID" was developed as an experimental platform for research about human swimming. SWUMANOID had a detailed human body shape, created using three-dimensional scanning and printing equipment, and was developed as an experimental model substituting for human subjects. Not only the appearance but also the methodology to realize various swimming strokes was considered. In order to reproduce complicated swimming motions with high fidelity, 20 waterproof actuators were installed. The free swimming of the crawl stroke at a velocity of 0.24 m/s was realized in the previous study. However, it could not perform the breaststroke due to mechanical limitations. The objectives of this study were to realize the breaststroke for SWUMANOID by improving its lower limbs, and to investigate the swimming performance of the breaststroke experimentally. The lower body of SWUMANOID was fully redesigned, built, and connected to the upper body. The swimming motion of the breaststroke was created based on that of an actual swimmer. A free swimming experiment was conducted in a 25 m outdoor swimming pool. In addition, in order to discuss the experimental results in detail, the experiment was reproduced by the simulation. From the experiment, it was found that SWUMANOID could perform the breaststroke successfully. The swimming speed for the stroke cycle of 2.3 s was found to be 0.12 m/s. Since this swimming speed was considered low compared to that of the actual swimmer, the reason for the discrepancy was examined by simulation. From the simulation, it was found that one main reason for the low swimming speed was insufficient output power of the motors, especially for the knee and shoulder joints.